Effects of the Children's Health Insurance Reauthorization Act on immigrant children's healthcare access. (15th September 2022) - Chu, Jun; Roby, Dylan H.; Boudreaux, Michel H.
Abstract: Objective: To estimate the effects of Children's Health Insurance Reauthorization Act (CHIPRA), a policy that provided states the option to extend Medicaid/CHIP eligibility to immigrant children who have not been legal residents for five years or more, on insurance coverage, access, utilization, and health outcomes among immigrant children. Data Sources: Restricted use 2000–2016 National Health Interview Survey (NHIS). Study Design: We used a difference‐in‐differences design that compared changes in CHIPRA expansion states to changes in non‐expansion states. Data Collection: Our sample included immigrant children who were born outside the US, aged 0–18 with family income below 300% of the Federal Poverty Level (FPL). Subgroup analyses were conducted across states that did and did not have a similar state‐funded option prior to CHIPRA (state‐funded vs. not state‐funded), by the length of time in the US (5 years vs. 5–14 years), and global region of birth (Latin American vs. Asian countries). Principle Findings: We found that CHIPRA was associated with a significant 6.35 percentage point decrease in uninsured rates (95% CI: −11.25, −1.45) and an 8.1 percentage point increase in public insurance enrollment for immigrant children (95% CI: 1.26, 14.98). However, the effects of CHIPRA became small and statistically not significant 3 years after adoption. Effects on public insurance coverage were significant in states without state‐funded programs prior to CHIPRA (15.50 percentage points; 95% CI:8.05, 22.95) and for children born in Asian countries (12.80 percentage points; 95% CI: 1.04, 24.56). We found no significant changes in health care access and utilization, and health outcomes, overall and across subgroups due to CHIPRA. Conclusions: CHIPRA's eligibility expansion was associated with increases in public insurance coverage for low‐income children, especially in states where CHIPRA represented a new source of coverage versus a substitute for state‐funded coverage. However, we found evidence of crowd‐out in certain subgroups and no effect of CHIPRA on access to care and health. Our results suggest that public coverage may be an important tool for promoting the well‐being of immigrant children but other investments are still needed.